Reflections on Social Demographic Ideas of Amir Khosrow Dehlavi in a Realistic Narrative - Reza Kiani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Among the books of Amir Khosrow Dehlavi, the famous Indian thinker and writer, there is a book that has serious differences with his other works, and it is really brilliant. This book is called Dolarani and Khezer Khan, despite its great cultural and social significance, it is an anonymous work in Iran. In this work, Amir Khosrow, while telling a love story, has briefly narrated how Islam was spread and expanded by the kings of the Ghori dynasty in India. There are important sources from the spread of Islam to Iran, but perhaps we have read and heard less about its spread to other countries, especially those with strong indigenous and patriotic civilizations. In this work, while narrating one of the Indian emotional stories, special attention is paid to the changed social, political and even cultural conditions of that time in India. The purpose of this study is to introduce and recognize this lesser known but important work, and to recognize the content by emphasizing its social paradigms. Documentary and library methods have been used to obtain the results. Findings show us that the new religion has changed some of the beliefs, traditions and social rituals of the people of that land, such as marriage in a Muslim way, attention to marriage and family formation within a group, and so on.